Da li shi nü hai = ΓΡAΦΩ - Goddess of powerlifting - Chiang, I-Tsun; Maoyu (Deng dai tian shi xi lie, 2021)
Hercules thought he lost his entire family after completing The Twelve Labours. Fortunately, his sister Athena foresaw it and hid his daughter Grapho in the world for him. Although Grapho cannot walk, she has other strengths. What will Grapho use her special ability to create her new life for?